Major and Minor Causes of Geophagy–Lithophagy in Animals and Humans - Alexander M. Panichev; Kirill S. Golokhvast (Geosciences)
The analyzed data set on the problem of geophagy–lithophagy shows that the instinctive desire, preserved in many groups of animals and humans, to eat mineral–crystalline substances—products of hypergenic transformation of various rocks in the most general form—is a manifestation of an evolutionarily conditioned universal way of regulating the material composition of the internal environment, as well as of many biological and physiological processes in the body. The effect of minerals on the organism can be divided into their main and secondary functions. The main cause of geophagy–lithophagy in animals and humans all over the world is the regulation of concentration and the ratio of rare earth elements in the neuroimmunoendocrine system, which controls metabolic processes and provides immune defense of the body. More than ten secondary causes of consumption of rare earth elements have been identified. In this review, we have attempted to summarize the data that we have collected on the causes of the phenomenon of the consumption of earth substance that we have identified in humans and various animal groups.